The Renaissance of African Spiritualities vis-à-vis Christianity: Adopting the Model of Mutual Enrichment: - Nweke, Kizito Chinedu (Studies in religion, 2019)
Christianity has been dominant in many parts of Africa especially since its colonial contact. Recently, however, there is a surge of interest in reviving indigenous spiritualities among Africans, both in Africa and in the diaspora. In Lagos, Nigeria, for example, shrines compete with churches and mosques for adherents and positions. Among the Igbos, a form of convenient interreligiousness has been developed in the society. When issues of practical expediency arise, the Christian would have the option of referring back to his/her traditional religion. Beyond Africa, the rise of African spiritualities has become conspicuous. For various reasons, ranging from Afrocentrism to anti-religious tendencies to the popular religions, from racial animosity to politico-economic ideologies, a lot of people, Africans and non-Africans, are embracing the neo-African spiritualities. This article is a study addressing this revival, by critically analyzing the reasons for its re-emergence, the challenges that have accompanied the revival and the implications of it in the Christian-African spirituality relationship. Can this renaissance in African spirituality bring forth or support a renaissance in Africa? Africa has about 450 million Christians, about 40% of the continent's population. People of African origin equally make up a good number of Christians outside Africa. In other words, Christianity is decisive, ideologically and structurally, not just as a religion but also in the socio-political life of Africans. Finding a way to harmonize Christianity and African spiritualities, especially in the face of this renaissance, for the growth of Africa, is the aim of this article. Hence, it suggests the model of "Mutual Enrichment."